Radiographs Detect Dorsal Scaphoid Translation in Scapholunate Dissociation - Chan, Kevin; Vutescu, Emil S.; Wolfe, Scott W.; Lee, Steve K. (Journal of Wrist Surgery, 2019)
Background Dorsal translation of the proximal scaphoid pole onto the rim of the distal radius is a late finding associated with chronic scapholunate instability. Dorsal scaphoid translation (DST) has been identified by magnetic resonance imaging in patients with scapholunate dissociation (SLD).Purpose The authors proposed to determine whether DST can be reliably detected on radiographs using two different measurement techniques.Patients and Methods Lateral radiographs of 20 patients with operatively confirmed SLD were compared with 20 uninjured patients in blinded assessment. DST was assessed using the concentric circle and dorsal tangential line methods. Reliability was calculated using intraclass correlation (ICC) values.Results Using both techniques, the scaphoid demonstrated increased dorsal translation in patients with SLD. Inter-rater reliabilities for the concentric circles and dorsal tangential line method on radiographs had ICCs > 0.80. Similarly, intra-rater reliabilities had ICCs > 0.90.Conclusions Both the concentric circles and dorsal tangential line techniques had excellent reliabilities, but the dorsal tangential line method is clinically more practical.Type of Study/Level of Evidence This is a Level III, diagnostic study.
Keywords: dorsal scaphoid translation; scapholunate dissociation; scapholunate interosseous ligament